2019
DOI: 10.1097/md.0000000000015987
|View full text |Cite
|
Sign up to set email alerts
|

The trim-and-fill method for publication bias: practical guidelines and recommendations based on a large database of meta-analyses

Abstract: Publication bias is a type of systematic error when synthesizing evidence that cannot represent the underlying truth. Clinical studies with favorable results are more likely published and thus exaggerate the synthesized evidence in meta-analyses. The trim-and-fill method is a popular tool to detect and adjust for publication bias. Simulation studies have been performed to assess this method, but they may not fully represent realistic settings about publication bias. Based on real-world meta-analyses, this arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
322
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 483 publications
(325 citation statements)
references
References 47 publications
2
322
0
1
Order By: Relevance
“…The trim and fill method is a statistical approach aimed to estimate potential missing studies, causing the asymmetry of the funnel plot. This method assumes that the studies with the most extreme ES have to be suppressed, adjusting the overall effect estimate [25]. To perform the meta-analysis, the software Prometa3 ® (Internovi, Italy) was used.…”
Section: Resultsmentioning
confidence: 99%
“…The trim and fill method is a statistical approach aimed to estimate potential missing studies, causing the asymmetry of the funnel plot. This method assumes that the studies with the most extreme ES have to be suppressed, adjusting the overall effect estimate [25]. To perform the meta-analysis, the software Prometa3 ® (Internovi, Italy) was used.…”
Section: Resultsmentioning
confidence: 99%
“…The symmetry of funnel plots was appraised by the Egger's test. The trim-and-fill method was used to estimate the number of potentially missing studies stemming from publication bias (21). Significant publication bias was recorded if the probability of the Egger's test is <10%.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…4). Further verification by the trim-and-fill method showed that, although publication bias may exist, our results were robust [35].…”
Section: Resultsmentioning
confidence: 74%